MAKING PREGNANCY A MISSED OPPORTUNITY FOR TREATMENT OF TUBERCULOSIS INFECTION : A SYSTEMATIC REVIEW - Atmaja, Sardjana; Gumilar, Gulam (Jurnal Ilmu Kesehatan dan Kesehatan, 2021)
Background : Eleven million Americans, representing 4% of the U.S. general population, are estimated to have latent tuberculosis infection (LTBI). In countries with low TB incidence, immigrant from higher incidence countries form the major pool of infected individuals. To understand the prevalence, screening and management of TBI in pregnancy. Methods : A systematic review of 4 databases (Embase, Embase Classic, Medline, Cochrane Library) covering articles published from January 1st 2010 to April 30th 2018. Articles in English with relevant information on prevalence, screening strategies and treatment of TBI during pregnancy were eligible for inclusion. Results : Of 193 titles initially identified, 108 abstracts were eligible for review. Of these, 86 articles qualified for full text review and 22 were retained: 3 cohort studies, 2 case-control studies, and 17 cross-sectional studies. In the USA, the estimated prevalence of TBI ranged from 14 to 48% in women tested, and tuberculin skin test (TST) positivity was associated with ethnicity. The proportion of women who attended follow-up visits after positive tuberculin tests varied from 14 to 69%, while 5 to 42% of those who attended follow-up visits completed a minimum of 6 months of isoniazid treatment. One study raised the possibility of an association of pregnancy/post-partum state with INH hepatitis (risk ratio 2,5, 95% CI 0.8–8.2) and fatal hepatotoxicity (rate ratio 4.0, 95% CI 0.2–258). One study deemed INH safe during breastfeeding based on peak concentrations in plasma and breast milk after INH administration. Conclusion : Pregnancy is an opportunity to screen for TBI. Interferongamma release assays are likely comparable to tuberculin skin tests and may be used during pregnancy. Efforts should be made to improve adherence with follow-up and treatment post-partum. Further data are needed with respect to safety and feasibility of antepartum INH therapy, and with respect to alternative treatment regimens.